Modified Bottle Cap for Improving Children’s Arithmetic Ability - Syaiputra Wahyuda Meisa Diningrat; Janah, Luluk; Mardiyah, Sakinatul (JURNAL PENDIDIKAN USIA DINI, 2019)
The preliminary study showed that the main problem, however, faced by kindergarten students are lack of mathematics skill, such arithmetic ability in kindergarten Galis. Therefore, the present study aims to investigate the effectiveness of a modified bottle cap as an educational game tool towards enhancement of arithmetic ability. Samples were prepared for the quasi-experiment research design involving 60 children, aged 4-5 years. A detailed comparison is made between the experimental condition, consisted of 30 students, received the educational game tool activities and the control condition which consisted of 30 students, received the instructional activities as usual. Before and after two weeks of the intervention with the game tool of a modified bottle cap, measures of arithmetic ability were administered to either experiment or control class. The results of the study indicated that in the experiment class, children’s arithmetic ability increased significantly compared to children in the control class. The differences may have been due to the intervention. To conclude, the modified bottle cap as an educational game tool effective to improve children’s mathematics skill, especially for arithmetic ability. However, the findings required the extended study on other research methods and the bigger size of the samples. Keywords: Early Childhood, Modified bottle cap, Early Arithmetic Ability. References: Aqib, Zainal. (2010). Belajar dan Pembelajaran di Taman Kanak-Kanak. Bandung: Yrama Widya. Arsyad, A. (2017). Media Pembelajaran. PT Raja Grafindo Pursada. Aunio, Pirjo; Tapola, Anna; Mononen; and Niemivirta, M. (2016). Early Mathematics Skill Development, Low Performance, and Parental Support in the Finnish Context. In Blevins-Knabe; A.M.B. Austin (Ed.), Early Childhood Mathematic Skill Development in the home environment. Cham, Switzerland: Springer. Ayuni, D., & Setiawati, F. A. (2019). Kebun Buah Learning Media for Early Childhood Counting Ability. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 3(1), 1. https://doi.org/10.31004/obsesi.v3i1.128 Barblett, L., Knaus, M., & Barratt-Pugh, C. (2016). The Pushes and Pulls of Pedagogy in the Early Years: Competing Knowledges and the Erosion of Play-based Learning. Australasian Journal of Early Childhood, 41(4), 36–43. https://doi.org/10.1177/183693911604100405 Barth, H., La Mont, K., Lipton, J., & Spelke, E. S. (2005). Abstract number and arithmetic in preschool children. Proceedings of the National Academy of Sciences of the United States of America, 102(39), 14116–14121. https://doi.org/10.1073/pnas.0505512102 Blevins-Knabe, B. (2016). Early Mathematical Development : How the Home Environment Matters. In Belinda Blevins-Knabe; Ann M. Berghout Austin (Ed.), Early Childhood Mathematics Skill Development in the Home Environment (pp. 8–9). Cham, Swutzerland: Springer. Copley, J. V. (2016). The Young Child and Mathematics. In M. Hogarty (Ed.), Numbers and Stories: Using Children’s Literature to Teach Young Children Number Sense (Second, pp. 1–14). https://doi.org/10.4135/9781483330907.n1 Depdiknas. (2005). Pedoman Pembelajaran di Taman Kanak-Kanak. Jakarta: Direktorat Pembinaan Taman Kanak-Kanak Sekolah Dasar. Depdiknas. (2007). Modul Pembuatan dan Penggunaan APE anak Usia 2-6 Tahun. Jakarta: Dirjen Pendidikan Luar Sekolah Direktorat PAUD. Dunekacke, S., Jenßen, L., Eilerts, K., & Blömeke, S. (2016). Epistemological beliefs of prospective preschool teachers and their relation to knowledge, perception, and planning abilities in the field of mathematics: a process model. ZDM - Mathematics Education, 48(1–2), 125–137. https://doi.org/10.1007/s11858-015-0711-6 Elizabeth, W. (2011). Cross-curricular Teaching to Support Child-initiated Learning in EYFS and KEY Stage I. In Suzanne and Kristine (Ed.), Early Childhood Educaiton: Yesterday, Today, and Tomorrow. New York: Routledge. Fitri, F., & Syamsudin, A. (2019, May). The Effectiveness of Race Track Games on Counting Ability and Child Learning Motivation. https://doi.org/10.2991/icsie-18.2019.78 Grindheim, L. T. (2017). Children as playing citizens. European Early Childhood Education Research Journal, 25(4), 624–636. https://doi.org/10.1080/1350293X.2017.1331076 Guslinda; Kurnia, R. (2018). Media Pembelajaran Anak Usia Dini. Surabaya: Jakad Publiser. Harris, B., & Petersen, D. (2017). Developing Math Skills in Early Childhood. Issue Brief. Mathematica Policy Research, Inc., (February), 1–6. Retrieved from http://ezproxy.library.uvic.ca/login?url=http://search.ebscohost.com/login.aspx?direct=true&db=eric&AN=ED587415&site=ehost-live&scope=site Haskell, S. H. (2000). The determinants of arithmetic skills in young children: Some observations. European Child and Adolescent Psychiatry, 9(SUPPL. 2), 77–86. https://doi.org/10.1007/s007870070011 Hurlock, Elisabeth, B. (1978). Perkembangan Anak, Jilid 2. Jakarta: Erlangga. Ismail, A. (2006). Education Games “Menjadi Cerdas dan Ceria dengan Permainan Edukatif.” Jacobi-Vessels, J. L., Todd Brown, E., Molfese, V. J., & Do, A. (2016). Teaching Preschoolers to Count: Effective Strategies for Achieving Early Mathematics Milestones. Early Childhood Education Journal, 44(1), 1–9. https://doi.org/10.1007/s10643-014-0671-4 Johnson, J. E., & Wu, M.-H. (2019). Perspectives on Play in Early Childhood Care and Educaiton. In M. B. Brown, Christopher; McMullen (Ed.), The Wiley Handbook of Early Childhood Care and Education (1st ed., p. 86). New Jersey: John Wiley & Sons. Kamus Besar Bahasa Indonesia Online. (2019). Retrieved from https://www.kamusbesar.com/prefix/nd Khasanah, I. (2013). Pembelajaran Logika Matematika Anak Usia Dini (Usia 4-5 Tahun) di TK Ikal Bulog Jakarta Timur. In Jurnal Penelitian PAUDIA (Vol. 2). Lai, N. K., Ang, T. F., Por, L. Y., & Liew, C. S. (2018). The impact of play on child development - a literature review. European Early Childhood Education Research Journal, 26(5), 625–643. https://doi.org/10.1080/1350293X.2018.1522479 Malapata, E., & Wijayanigsih, L. (2019). Meningkatkan Kemampuan Berhitung Anak Usia 4-5 Tahun melalui Media Lumbung Hitung. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 3(1), 283. https://doi.org/10.31004/obsesi.v3i1.183 Manjale, N. B., & Abel, C. (2017). Significance and adequacy of instructional media as perceived by primary school pupils and teachers in. 4(6), 151–157. Martin, R. B., Cirino, P. T., Sharp, C., & Barnes, M. (2014). Number and counting skills in kindergarten as predictors of grade 1 mathematical skills. Learning and Individual Differences, 34, 12–23. https://doi.org/10.1016/j.lindif.2014.05.006 Naz, A. A., & Akbar, R. A. (2010). Use of Media for Effective Instruction its Importance : Some Consideration. Journal of Elementary Education, 18(1–2), 35–40. OECD. (2019). Mathematics Performance (PISA) 2015. https://doi.org/10.1787/04711c74-en Papadakis, S., Kalogiannakis, M., & Zaranis, N. (2017). Improving Mathematics Teaching in Kindergarten with Realistic Mathematical Education. Early Childhood Education Journal, 45(3), 369–378. https://doi.org/10.1007/s10643-015-0768-4 Passolunghi, M. C., Cargnelutti, E., & Pellizzoni, S. (2019). The relation between cognitive and emotional factors and arithmetic problem-solving. Educational Studies in Mathematics, 100(3), 271–290. https://doi.org/10.1007/s10649-018-9863-y Preeti. (2014). Education and role of media in education system. International Journal of Scientific Engineering and Research, 2(3), 174–175. Rahman, S. (2010). Alat Permainan Edikatif untuk Program PAUD. Palu: Tadulako University Press. Rohmah, N., & Waluyo, E. (2014). Arithmetic Dice Media as Counting Concept Introduction for Early Childhood. Naili Rohmah & Edi Waluyo / Indonesian Journal of Early Childhood Education Studies, 3(2), 127–133. https://doi.org/10.15294/ijeces.v3i2.9486 Rushton, S. (2011, June). Neuroscience, Early Childhood Education and Play: We are Doing it Right! Early Childhood Education Journal, 39(2), 89–94. https://doi.org/10.1007/s10643-011-0447-z Schacter, J., & Jo, B. (2017). Improving preschoolers’ mathematics achievement with tablets: a randomized controlled trial. Mathematics Education Research Journal, 29(3), 313–327. https://doi.org/10.1007/s13394-017-0203-9 Schwartz, S. (2005). Teaching YoungChildren Mathematics. Westport, Connecticut: Praeger. Selvi, K. (2010). Teachers’ competencies. Cultura. International Journal of Philosophy of Culture and Axiology, 7(1), 167–175. https://doi.org/10.5840/cultura20107133 Smaldino, S. E., Russel, J. D., & Lowther, D. L. (2014). Instructional Technology & Media for Learning (9th ed.). Jakarta: Kencana Prenada Media Group. Suryadi. (2007). Cara Efektif Memahami Perilaku Anak Usia Dini. Jakarta: Edsa Mahkota. Vogt, F., Hauser, B., Stebler, R., & Rechsteiner, K. (2018). Learning through play – pedagogy and learning outcomes in early childhood mathematics. 1807. https://doi.org/10.1080/1350293X.2018.1487160 Vogt, F., Hauser, B., Stebler, R., Rechsteiner, K., & Urech, C. (2018). Learning through play–pedagogy and learning outcomes in early childhood mathematics. European Early Childhood Education Research Journal, 26(4), 589–603. https://doi.org/10.1080/1350293X.2018.1487160 Wati, E. R. (2016). Ragam Media Pembelajaran (A. Jarot, Ed.). Yogyakarta: Kata Pena. Zulkardi, N. (2011). Building counting by traditional game: A Mathematics Program for Young Children. IndoMs. J.M.E, 2(1), 41–54.